Literature Review: The Effect of Zeaxanthin Carotenoid Supplementation on the Prevention of Age-Related Macular Degeneration (AMD) - Indah Dwi Utami; Trias Mahmudiono (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Age-Related Macular Degeneration (AMD) is a condition that harms the retina and primarily affects those who are 60 years old or older, leading to significant vision loss. In the United States, the count of individuals affected is projected to rise from 9.1 million in 2010 to approximately 17.8 million by the year 2050. The progression of AMD can be prevented by consuming sources of antioxidants which have been proven to inhibit the development of this disease. One type of antioxidant that is easy to find and abundant in nature is the carotenoid zeaxanthin.Objectives: This study aimed explore the connection between the administration of carotenoid zeaxanthin and the prevention of Age-Related Macular Degeneration (AMD).Methods: This research used a literature review method on research articles that have been conducted previously. Search for articles using the online databases PubMed and Sciencedirect. journal inclusion criteria for the last 5 years. A total of 5 articles were used in this study.Results: The use of the carotenoid zeaxanthin showed a positive effect on preventing the development of Age-Related Macular Degeneration (AMD), yielding significant outcomes (p<0.05).Conclusions: Administration of zeaxanthin supplementation has an effect on inhibiting the occurrence of Age-Related Macular Degeneration (AMD)